Redesigning Laboratory Courses in Information Technology Program: An Inquiry Based Learning Approach - S, Thiruchadai Pandeeswari.; Chandrasekaran, Jeyamala; S, Pudumalar. (Journal of Engineering Education Transformations, 2025)
Laboratory courses in Information Technology programs are pivotal for hands-on learning and skill development. They prepare students for real-world applications, nurture critical thinking and teamwork, and offer practical problem-solving experiences. These courses bridge the gap between theory and practice, helping students become industry-ready and ethical technology professionals. However, challenges in the conduct of laboratory courses include limited access to resources like computers and software, maintaining up-to-date content in a rapidly evolving field, addressing diverse student backgrounds and abilities, preventing plagiarism and cheating, and managing large class sizes efficiently. These challenges can impact the quality of hands-on learning, require effective teaching strategies, and demand careful planning and adaptation to ensure a productive learning environment. Inquiry-based learning (IBL) is an educational approach that centers on active student engagement and exploration. It involves students posing questions, problems, or scenarios and then actively seeking answers or solutions through research, investigation, and critical thinking. Inquiry based learning, when implemented in lab courses promises to promote connection to the real-world problems, problem solving skills and application of engineering knowledge to solve complex problems. In this paper, a hybrid inquiry based approach is adapted for the conduct of three laboratory courses in B.Tech Information Technology Program. The implementation was experimented over different batches of around 390 students. The proposed approach resulted in significant improvement of the attainment of course outcomes. It also had profound impact on the transferable skills of the learners such as critical thinking, problem solving skills, attention to detail and management skills. The impact of the proposed approach is measured and the quantitative results demonstrate the effectiveness of the proposed instructional design.